Nghiên cứu ý định sử dụng dịch vụ giao đồ ăn trực tuyến của giới trẻ Hà Nội trong thời kỳ dịch COVID-19 - Phạm Đức , Anh; Trần Thu , Hà; Trần Hương , Thảo; Nguyễn Thùy , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study empirically examines the main factors affecting the behavioral intention of young people to use online food delivery (OFD) services under the COVID-19 epidemic in Hanoi. Based on a survey of 270 respondents from local high schools and economics universities, the structural equation model (SEM) results validated 6 key predictors of the behavioral intention of OFD service users, specifically: (i) Convenience, perceived control, and customer service have significant positive impacts on customer satisfaction; (ii) Usefulness, food quality, and customer satisfaction tend to stimulate customer’s intention to use OFD. From these findings, the study proposed recommendations on service quality improvement for OFD providers, restaurants, and delivery companies to better reach young customers during the pandemic era.